Relationship of Individual Characteristics and Behavior with the Tuberculosis Prevalence in Kupang City - Wanti; Ety Rahmawati; Sisilia Leny Cahyani; Debora G Suluh; Enni Rosida Sinaga; Agustina Agustina; Siprianus Singga (proceedinginternational, 2023)
It is estimated that one-third of the world's population has been infected by TB germs, and Indonesia is in the top 3rd ranks with the most cases in the world. Many factors are associated with the incidence of TB so this study aims to determine the factors associated with the incidence of Tuberculosis. This analytic observational study used a case-control study design. The study was carried out in Kupang City in 2021. The case sample was 75 cases of TB patients undergoing treatment during the study, while the control sample was 75 non-TB patients around the control house. The dependent variable was the tuberculosis prevalence, while the independent variable was are age, gender, knowledge, attitude, smoking habits, cigarettes per day. The data were collected by interview and then the data were analyzed by univariate and bivariate by chi square test. This study found variables related to the incidence of TB, namely knowledge (p 0.049 <0.05; OR 2.03; 95% CI: 1.056 – 3.909), attitude (p 0.001 <0.005; OR 3.50; 95% CI: 1.695–7.228), smoking behavior (p 0000<0.005; OR 4,447; 95% CI: 2.174 – 9.094), and smoking 10 cigarettes per day (p 0.000<0.05; OR 7.731; 95% CI: 3.265-18.302) . While the variables that are not related to the incidence of TB are age (p 0.513>0.05, 95% CI: 0.403-1.454) and gender (p 0.250>0.05; C 95%: 0.338-1.239). The greatest risk of tuberculosis is smoking behavior >10 cigarettes per day, namely 7.731 and followed by smoking and attitude variables, while lack of knowledge has the lowest risk of suffering from tuberculosis, which is 2.032. It is necessary to intensify outreach to the community to increase knowledge and attitudes in preventing tuberculosis transmission and counseling about the impact of smoking on the risk of tuberculosis incidence so that it is expected to reduce the number of smokers and the number of TB cases in the community.